THE SINO – US RELATIONSHIP : STUDI KASUS KEBIJAKAN AMERIKA SERIKAT TERHADAP ONE CHINA POLICY - Arthur Wabiser, Yosias Marion (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 1 No 03 (2015), 2015)
ABSTRACT Taiwan and china beginning conflict when the difference integrity of the two nations who desire full sovereignty to in a single nation and China making a policy of "one China policy" that is approved the two nations. when the United States established diplomatic relations with Taiwan, China considers Taiwan as a barrier Relations PRC and the United States, and in violation of the agreement "One China Policy". This research uses descriptive method, with the concept of Strategic ambiugity Keyword: China,Taiwan,US,One China policy,strategic ambiugity